1986
DOI: 10.1088/0029-5515/26/2/001
|View full text |Cite
|
Sign up to set email alerts
|

The physics of burn in magnetized deuterium-tritium plasmas: spherical geometry

Abstract: There is a large region of density-temperature space in which the effects of a magnetic field on heat transport and alpha-particle mobility are significant and the magnetic pressure is small compared with the pressure of a deuterium-tritium plasma. Spherical fusion burn in this regime is examined. It is found that for volume burn, magnetic fields can greatly increase the yield. In regimes where propagating burn does not occur, the burn can be enhanced by a magnetic field. In regimes where propagating deflagrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 4 publications
0
26
0
Order By: Relevance
“…The primary attraction to any MIF fusion scheme is that the power required to drive these slow velocity implosions is significantly smaller than required for standard ICF and could potentially offer a low cost approach to fusion 16 . Jones and Mead 17 performed detailed numerical simulations of spherical capsules, which supported the conclusion that a magnetic field could improve volume burn of a deuterium-tritium (DT) gas. However, they also showed that a magnetic field tended to inhibit the propagation of a burn wave into a surrounding layer of cold dense DT.…”
mentioning
confidence: 77%
“…The primary attraction to any MIF fusion scheme is that the power required to drive these slow velocity implosions is significantly smaller than required for standard ICF and could potentially offer a low cost approach to fusion 16 . Jones and Mead 17 performed detailed numerical simulations of spherical capsules, which supported the conclusion that a magnetic field could improve volume burn of a deuterium-tritium (DT) gas. However, they also showed that a magnetic field tended to inhibit the propagation of a burn wave into a surrounding layer of cold dense DT.…”
mentioning
confidence: 77%
“…The fields, if large enough, could reduce the R-T growth rate (Section 2.3). The magnetic fields, amplified in the fuel by plasma compression, could greatly increase the yield (Jones & Mead 1986). The challenge is to understand and to represent the complex magnetic contributions (Sections 2 and 3) with sufficient accuracy to predict actual pellet performance.…”
Section: Relevance To Inertial Confinement Fusionmentioning
confidence: 99%
“…Using a magnetic field to enhance inertial fusion is an old idea (Jones & Mead 1986) receiving renewed interest (Slutz & Vesey 2012). An imposed field is being investigated at LLNL as a way to improve capsule performance and achieve ignition on the National Ignition Facility (NIF) (Perkins et al 2013(Perkins et al , 2014D.…”
Section: Introductionmentioning
confidence: 99%